Contributors to the neonate’s death in the intensive care unit - Mustafa Kamal , Ahmed; Zuhair Naama , Khalid; Subhi Talab, Hossam (Diyala Journal of Medicine, 2023)
Background: Iraq had the third-greatest neonatal mortality rate in the Middle East in 2021 with 14 fatalities per 1,000 live births. Objective: To investigate factors contributing to poor outcomes in the neonatal intensive care unit. Patients and Methods: A retrospective cohort study conducted between 1 April to 31 September 2022 involved 632 neonates. Required data and outcomes were collected using predesigned forms. Results: The mortality rate in NICU was 23.9%, with 64.9% of deaths occurring within the first six days. The overall mortality rate was 38.5 per 1000 live births. Deceased neonates had significantly lower gestational age and birth weight (P<0.001). Prematurity, respiratory distress syndrome, and congenital anomalies contributed to 94%, 73.5%, and 20.5% of deaths respectively. Mortality was significantly higher in patients with RDS 111(56.3%; P<0.001), pulmonary hemorrhage nine (100%; P<0.001), sepsis 26 (74.3%; P<0.001), and chorioamnionitis nine (100%, P=0.002). Newborns delivered vaginally had a 4.11 times higher likelihood of poor outcomes compared to cesarean deliveries. Conclusion: Most NICU deaths resulted from prematurity and respiratory distress syndrome. Enhancing healthcare personnel skills, standardizing protocols, and evidence-based practices for preterm and respiratory 0distress syndrome management can help reduce neonatal mortality rates in Iraq.